Peranan Promosi Media Sosial, OTA, dan Ulasan Tamu terhadap Keputusan Berkunjung di Hotel Nite&Day Surabaya - Mohamad Syaiful; Titin Hargyatni (MAMEN: Jurnal Manajemen, 2026)
Tight rivalry among accommodation providers forms the background of this study, prompting Hotel Nite & Day Surabaya to rely on social media promotion, Online Travel Agent (OTA) platforms, and guest reviews as marketing instruments that shape the decision to visit. The objective is to examine how far each of these variables, both separately and jointly, contributes to the visiting decision of guests at Hotel Nite & Day Surabaya. A quantitative design was applied through a survey of 100 respondents obtained by purposive sampling. Questionnaires served as the data collection instrument, while the analysis relied on multiple linear regression accompanied by t-tests, an F-test, and the coefficient of determination. The findings reveal that social media promotion (t = 3,440), OTA (t = 4,009), and guest reviews (t = 3,195) each exert a positive and significant influence on the decision to visit. The F-test produced a significance value of 0,000 (<0,05), whereas an Adjusted R-Square of 0,911 shows that 91,1% of the variation in the decision to visit is explained by these three variables. All hypotheses proposed in this study are therefore accepted.